Introduction to Corrosion - Basics and Advances 2023
DOI: 10.5772/intechopen.110161
|View full text |Cite
|
Sign up to set email alerts
|

Small Organic Molecule as Corrosion Inhibitors for Mitigating Metal Corrosion

Abstract: Metal corrosion constitutes degradation of metals in the presence of favorable corrosive atmosphere. It worsens metal quality. The prevention of metal corrosion is so significant to save metals for their better utility. Corrosion inhibitors are widely used for the mitigation of metal corrosion. Small organic molecules as corrosion inhibitors are showed prominent corrosion inhibitive property because of their unique electron donating capacity to the metal orbitals. The bonding occurred between organic molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Studies found that functional groups, bonding and molecular sizes of atoms in organic inhibitors, were the factors that effected their effectivity in reducing corrosion rate [13]. The interactions between organic 68 molecules and metal surfaces perform a critical role in reducing corrosion rates and increasing inhibition efficacy [14]. One of the resources for such molecules could be from plant extracts, which have been proven to effectively reduced corrosion rate in previous studies [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that functional groups, bonding and molecular sizes of atoms in organic inhibitors, were the factors that effected their effectivity in reducing corrosion rate [13]. The interactions between organic 68 molecules and metal surfaces perform a critical role in reducing corrosion rates and increasing inhibition efficacy [14]. One of the resources for such molecules could be from plant extracts, which have been proven to effectively reduced corrosion rate in previous studies [15], [16].…”
Section: Introductionmentioning
confidence: 99%